2016
DOI: 10.5702/massspectrometry.a0047
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Gingival Crevicular Fluid Using Gas Chromatography/Mass Spectrometry

Abstract: Periodontitis is one of the most prevalent threats to oral health as the most common cause of tooth loss. In order to perform e ective treatment, a clinical test that detect sites where disease activity is high and predicts periodontal tissue destruction is strongly desired, however, it is still di cult to prognose the periodontal tissue breakdown on the basis of conventional methods. e aim of this study is to examine the usefulness of gas chromatography/mass spectrometry (GC/MS), which could eventually be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 15 publications
3
31
0
Order By: Relevance
“…In previous studies, saliva, serum and gingival cervical fluid were confirmed to demonstrate molecular changes during the development of chronic periodontitis. Many metabolites associated with inflammation, oxidative stress, tissue degradation and bacterial metabolism were found significantly elevated in periodontal disease …”
Section: Introductionmentioning
confidence: 84%
“…In previous studies, saliva, serum and gingival cervical fluid were confirmed to demonstrate molecular changes during the development of chronic periodontitis. Many metabolites associated with inflammation, oxidative stress, tissue degradation and bacterial metabolism were found significantly elevated in periodontal disease …”
Section: Introductionmentioning
confidence: 84%
“…Untargeted metabolomics has been used to distinguish the metabolic signature of individuals with periodontal disease from that of healthy individuals . In addition, metabolic profiles have been used to discriminate between various stages and progression of periodontal disease.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Ozeki et al [48] reported on the efficacy of GC/MS that could be used to detect metabolites in GCF. GCF samples were collected from two diseased sites from each patient and from clinically healthy sites of volunteers.…”
Section: Discovery Of Periodontal Disease Biomarkers By Proteomic mentioning
confidence: 99%
“…GCF samples were collected from two diseased sites from each patient and from clinically healthy sites of volunteers. Overall, 19 metabolites were identified using GC/MS [48]. Total ion current chromatograms showed broad differences in the metabolite peak patterns between GCF samples obtained from healthy, moderate-, and deep-pocket sites.…”
Section: Discovery Of Periodontal Disease Biomarkers By Proteomic mentioning
confidence: 99%
See 1 more Smart Citation